Fixation of CO2 along with bromopyridines on a silver electrode. Issue 8 (15th August 2018) - Zhang, Yingtian; Yu, Shuxian; Luo, Peipei; Xu, Shisong; Zhang, Xianxi; Zhou, Huawei; Du, Jiyuan; Yang, Jie; Xin, Nana; Kong, Yuxia; Liu, Junhai; Chen, Baoli; et al.
Abstract : Resulting from the drastic increase of atmospheric CO2 concentration day by day, global warming has become a serious environmental issue nowadays. The fixation of CO2 to obtain desirable, economically competitive chemicals has recently received considerable attention. This work investigates the fixation of CO2 along with three bromopyridines via a facile electrochemical method using a silver cathode to synthesize picolinic acids, which are important industrial and fine chemicals. Cyclic voltammetry is employed to investigate the cyclic voltammetric behaviour of bromopyridines. In addition, systematic study is conducted to study the relationships between the picolinic acids' yield and the electrolysis conditions and intrinsic parameters. The results show that the target picolinic acids' yields are strongly dependent on various conditions such as solvent, supporting electrolyte, current density, cathode material, charge passed, temperature and the nature of the substrates. Moreover, in the studied electrode materials such as Ag, Ni, Ti, Pt and GC, electrolysis and cyclic voltammetry show that Ag has a good electrocatalytic effect on the reduction and carboxylation of bromopyridine. This facile electrochemical route for fixation of CO2 provides an indispensable reference for the conversion and utilization of CO2 under mild conditions.